Use of serious games in Higher Education: Kahoot! in Forensic Dentistry (Research, Society and Development, 2022)
The help of active methodologies promotes motivation and facilitates the understanding of the subjects taught in class. The use of games - gamification and serious games - have been widely used, especially with the addition of remote activities because of the Covid-19 pandemic. Kahoot! is a free question-and-answer platform that has gained a lot of popularity among teachers, and thus, this research aimed to contribute to increase knowledge about the content related to Forensic Dentistry developed on the Kahoot! platform, as well as to quantify the games and analyze the quality according to what they propose. A descriptive, quantitative study was conducted using public data from Kahoot! using the search terms "Legal Dentistry", "Forensic Dentistry", and "Forensic Dentistry", applying a language filter and individual analysis of each quiz to verify the relevance of the content addressed with the proposed theme. The results initially showed 159 quizzes, which after individual analysis resulted in 82 (48.4%) with content pertinent to the proposed theme, representing 51.6% of questionnaires with disagreement.   The term with the highest number of associated games was "Legal Dentistry", with 48 games. Of the total number of quizzes evaluated, 64.7% dealt with human identification. The conclusion was that there are a large number of games on Kahoot! that use the terms related to forensic dentistry, represented by 159 quizzes. However, a little more than half of them, 51.6%, did not present pertinent content to the title of the developed quiz, representing a limitation to the adequate use of the platform.